Effect of post length on endodontically treated teeth: analyses of tensile strength - Jefferson Ricardo Pereira; Accácio Lins do Valle; Fábio Kenji Shiratori; Janaina Salomon Ghizoni (Universidade Estadual de Campinas, 2015)
Aim: This study compared the tensile strength of endodontically treated teeth restored with different posts and cores with different post lengths. Methods: Sixty extracted intact canines were randomly divided into 6 groups. Groups CP1, CP2 and CP3 were restored with custom cast postand-core and groups PF1, PF2 and PF3 were restored with prefabricated post and composite resin core, with different combinations of post length of 5,0 mm, 7.5 mm and 10 mm, respectively (n = 10). All teeth were restored with a total metal crown. A tensile loading was applied at a 180- degree angle to the long axis until failure. Results: The 2-way analysis of variance (á=0.05) showed statistically significant difference (p<0.001) among the groups. However, when the mean fracture forces for the groups were compared (Groups 1, 2, 3, 4, 5 and 6: 134.5 N (34.2), 178.9N (40.1), 271,5 N (55.9), 161.7 N (22.0), 216.1 N (42.0) and 257.9 N (41.0), respectively), no significant differences could be detected among the groups restored with prefabricated post and cast post-and-core. It was found significant differences when it was compared the different lengths for each type of post (p<.05). Conclusions: This study showed that increasing post length significantly increased the tensile strength of prefabricated posts and cast post-and-core used in endodontically treated teeth. On the other hand, significant differences were not found when comparing endodontically treated teeth restored with custom cast post-and-cores or pre-fabricated posts and composite resin cores with the same post length.